Method for reducing alkalinity of pre-lithium silica surface
By mixing TiO2 with pre-lithiated SiO and then heat-treating it, the problem of increased alkalinity on the SiO surface in the solid-phase pre-lithiation method was solved, thus improving the electrochemical performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411430725.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-10
AI Technical Summary
The residual LiOH in the slurry preparation process of the solid-phase pre-lithiation method leads to an increase in the alkalinity of the SiO surface material of the lithium-ion battery anode, which affects the battery performance.
TiO2 was mixed with pre-lithiated SiO and subjected to heat treatment to convert surface residual alkali into electrochemically active lithium titanate.
It reduces the surface alkalinity of the negative electrode material, enhances ionic conductivity and electrochemical reactivity, and improves the initial coulombic efficiency and cycle performance of lithium-ion batteries.
Smart Images

Figure CN119297189A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery materials, and in particular relates to a method for reducing the alkalinity of the surface of pre-lithium silicon oxide. Background Art
[0002] Lithium-ion batteries have high specific capacity, long cycle life and stable operation, and have attracted much attention in recent decades. Graphite is the most commonly used material for lithium-ion battery negative electrodes, but research on graphite negative electrodes has now reached its upper limit, and its layered structure restricts the application of fast charging. In comparison, SiO has a higher specific capacity (2100mAh / g), better charge and discharge performance, and a more suitable working potential. Therefore, SiO is considered to be the most promising next-generation lithium-ion battery negative electrode material. However, the SiO negative electrode will react with active lithium ions during the first lithium insertion process to produce irreversible silicates (4SiO+17.2Li→3Li 4.4 Si+Li4SiO4), these irreversible reactions consume active lithium ions, resulting in a low first coulombic efficiency of the SiO negative electrode.
[0003] Pre-lithiation technology is one of the main methods to solve the low first coulombic efficiency of SiO. Among them, the solid-phase pre-lithiation method has become the most commonly used technology to improve the first coulombic efficiency of SiO due to its advantages such as simple process, environmental friendliness and low safety risk. The solid-phase pre-lithiation method mainly obtains the pre-lithiation product by mixing LiOH, Li2CO3 and LiH with SiO and performing dry heat treatment. However, the residual LiOH in the solid-phase pre-lithiation process will increase the pH value of the slurry during the slurry preparation process, which will cause side reactions of the binder and gas production, affecting the battery performance. Summary of the invention
[0004] The object of the present invention is to provide a method for reducing the alkalinity of the pre-lithium silicon oxide surface to overcome the above-mentioned disadvantages.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is: a method for reducing the alkalinity of the surface of pre-lithium silicon oxide, comprising the following steps:
[0006] S1, pre-lithiation treatment of SiO using lithium reagent;
[0007] S2, mixing the pre-lithiated SiO and TiO2;
[0008] S3. Heat-treating the mixed SiO and TiO2.
[0009] Furthermore, in S1, the lithium reagent is selected from any one or more of LiOH, Li2CO3, and LiH.
[0010] Further, in S1, the mass ratio of SiO to the lithium reagent is 10: 1 to 15: 1. Exemplarily, the mass ratio of SiO to the lithium reagent is 10: 1, 11: 1, 12: 1, 13: 1, 14: 1, 15: 1 or a range consisting of any two thereof.
[0011] Further, in S1, the pre-lithiation treatment temperature is 600-800°C for 3-6 hours. Exemplarily, the pre-lithiation treatment temperature is 600°C, 650°C, 700°C, 750°C, 800°C or a range consisting of any two thereof.
[0012] Furthermore, in S1, during the pre-lithiation treatment, nitrogen or argon is introduced as a protective gas.
[0013] Further, in S2, the mass ratio of SiO and TiO2 after pre-lithiation is 95 to 99:1 to 5. Exemplarily, the mass ratio of SiO and TiO2 is 95:5, 96:4, 97:3, 98:2, 99:1 or a range consisting of any two thereof.
[0014] Furthermore, in S2, the mass ratio of SiO and TiO2 after pre-lithiation is 98:2.
[0015] Further, in S3, the reaction temperature of the heat treatment process is 500-900°C, and the reaction time is 3-6h. Exemplarily, the reaction temperature of the heat treatment process is 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C or a range consisting of any two of them. If the reaction temperature of the heat treatment process is too low, the reaction will be incomplete and the alkaline substances will not be completely removed. If the reaction temperature is too high, it will cause side reactions in the SiO negative electrode material and reduce the content of active substances.
[0016] Further, in S3, the heating rate of the heat treatment process is 1-5°C / min. Exemplarily, the heating rate of the heat treatment process is 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, or a range consisting of any two thereof.
[0017] Furthermore, in S3, during the heat treatment process, nitrogen or argon is introduced as a protective gas.
[0018] The beneficial effect of the present invention is that the present invention adopts a method of mixing a small amount of TiO2 with pre-lithiated SiO, so that the residual alkali on the surface of the pre-lithiated SiO negative electrode material is in situ converted into electrochemically active lithium titanate. While reducing the alkalinity of the surface of the negative electrode material, its ion conductivity and electrochemical reaction activity are enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 It is a comparison diagram of the first cycle charge and discharge curves of Example 1 of the present invention and Comparative Example 1;
[0022] Figure 2 It is a comparison diagram of the cycle curves of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0024] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0025] The applicant discovered that TiO2 is an inorganic amphoteric oxide that can react with LiOH to form lithium titanate (Li4Ti5O 12 ). Therefore, the present invention provides a method for reducing the alkalinity of the pre-lithiation silicon oxide surface. For the high alkalinity of SiO after solid-state pre-lithiation, a method of mixing TiO2 with pre-lithiation SiO is adopted to convert the residual alkali on the surface of the pre-lithiation SiO negative electrode material into electrochemically active lithium titanate in situ. While reducing the alkalinity of the negative electrode material surface, its ion conductivity and electrochemical reaction activity are also enhanced.
[0026] The specific steps include:
[0027] S1. Pre-lithiation of SiO using lithium reagent
[0028] SiO2 and lithium reagent are uniformly mixed in a mass ratio of 10:1 to 15:1, and the mixture is transferred to a corundum crucible for heat treatment.
[0029] The corundum crucible containing the lithium reagent and SiO mixture is transferred to a tube furnace for pre-lithiation reaction. The reaction temperature during the pre-lithiation reaction is 600-900°C, the heating rate is 1-5°C / min, the reaction time is 3-6h, and then the temperature is naturally cooled to room temperature. Nitrogen or argon is used as a protective gas throughout the pre-lithiation reaction.
[0030] In some embodiments, the lithium reagent is selected from any one or more of LiOH, Li2CO3, and LiH.
[0031] S2. Mix the pre-lithiated SiO and TiO2, wherein the mass ratio of SiO and TiO2 is 95:5 to 99:1. Preferably, the mass ratio of the pre-lithiated SiO and TiO2 is 98:2.
[0032] S3. Heat-treating the mixed SiO and TiO2.
[0033] The mixture is transferred to a corundum crucible for heat treatment. The corundum crucible is transferred to a tube furnace for heat treatment. The reaction temperature of the heat treatment process is 500-900°C, the heating rate is 1-5°C / min, the reaction time is 3-6h, and then the temperature is naturally cooled to room temperature. Nitrogen or argon is used as a protective gas throughout the reaction process.
[0034] The preparation method of the lithium ion battery containing the above-mentioned alkali reduction treated pre-lithium silicon oxygen comprises the following steps:
[0035] Step 1: Mix the obtained silicon-oxygen negative electrode material with a conductive additive and a binder to prepare a slurry, and use water as a dispersant. When preparing the slurry, in order to evenly mix the components, a mixer is preferably used for sufficient mixing.
[0036] In some embodiments, the conductive additive is selected from one or more of carbon black, acetylene black, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene, and the mass ratio of the conductive additive to the negative electrode active material is 1 to 10 w.t.%.
[0037] In some embodiments, the binder is selected from at least one of sodium alginate, acrylic resin PAA, lithium polyacrylate LiPAA, sodium polyacrylate NaPAA, carboxymethyl cellulose CMC / styrene butadiene rubber SBR. The mass ratio of the binder to the negative electrode active material is 1 to 10 w.t.%.
[0038] Step 2: Use a coating machine to coat the obtained slurry on a copper foil current collector with a thickness of 4 to 15 μm, dry it, roll it, and cut it into appropriate sizes for later use.
[0039] Step 3: The positive electrode is prepared by a slurry coating process similar to that of the negative electrode. The positive electrode material includes one or more of the following substances:
[0040] a. Lithium-containing transition metal oxides, with the structural formula LiNi x Co y Mn 1-x-y O2(0≤x≤1,0≤y≤1) or LiNi x Co y Al 1-x-y O2 (0≤x≤1,0≤y≤1); for example, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.85 Co 0.1 Al 0.05 O2.
[0041] b. Multi-anion cathode materials, such as LiMPO4 (M = Fe or / and Mn, such as LiFePO4, LiFe 0.8 Mn 0.2 ).
[0042] The positive electrode current collector is generally made of aluminum, nickel, stainless steel, titanium, etc. or a composite foil formed by metal and non-metal. The coating dispersion solvent is generally a non-aqueous solvent, such as N-methylpyrrolidone (NMP), etc. The adhesive is generally a fluorine-containing polymer, such as polyvinylidene fluoride (PVdF).
[0043] Step 4: Place the negative electrode sheet and the separator (which separates the positive and negative electrode sheets and has micropores in the middle to transmit lithium ions) + , such as polyethylene or polypropylene film, etc.) and the positive electrode are assembled into a battery.
[0044] Step 5: Add electrolyte and then seal to obtain a lithium battery.
[0045] The electrolyte system is a non-aqueous electrolyte solution containing salts that is liquid at room temperature. The aprotic solvent used in the electrolyte includes at least one of dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), ethylene carbonate (VC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), etc., and at least one lithium-containing electrolyte salt that can be dissolved in the above solvent, such as lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorooxalate borate (LiODFB), lithium perchlorate (LiClO4), lithium bistrifluoromethanesulfonyl imide (LiTFSI), etc. The concentration of the electrolyte solution is preferably 0.8 to 2.0 mol / L. In addition, 0.1 to 3 w.t.% of a compound containing a carboxylic anhydride group, a compound containing sultones (such as propylene sultone, propane sultone) and the like, or a compound containing boron, etc. can also be added to the electrolyte. The purpose is to improve the chemical stability of the electrolyte and inhibit its decomposition on the surface of the negative electrode material.
[0046] The electrolyte system may also include some or all solid electrolyte components, such as organic solid electrolytes, oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, etc.
[0047] Example
[0048] The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0049] Example 1
[0050] S1. Pre-lithiation of SiO using lithium reagent
[0051] SiO and LiH were mixed evenly at a mass ratio of 15:1, and the mixture was placed in a corundum crucible. The corundum crucible was then transferred to a tube furnace, and argon was used as a protective gas throughout the process. The temperature was raised to 800°C at a rate of 5°C / min and kept at this temperature for 6 hours, and then naturally cooled to room temperature. After the reaction was completed, a pre-lithiated silicon-oxygen negative electrode material was obtained.
[0052] S2. Evenly mix the pre-lithiated silicon-oxygen negative electrode material and TiO2 at a mass ratio of 98:2.
[0053] S3. Heat-treating the mixed SiO and TiO2.
[0054] The mixture was placed in a corundum crucible, and the corundum crucible was transferred to a tube furnace, and the temperature was raised to 850°C at a rate of 5°C / min with argon as protective gas throughout the process, and then naturally cooled to room temperature. After the reaction was completed, a pre-lithium silicon-oxygen negative electrode material treated with alkali reduction was obtained.
[0055] Example 2 (Changing the mass ratio of SiO and LiH)
[0056] The process steps of Example 2 and Example 1 are basically the same, the main difference is that in Example 2, the mass ratio of SiO and LiH is changed from 15:1 to 12:1 during the pre-lithiation process, and the other experimental conditions remain unchanged.
[0057] Example 3 (Changing the pre-lithiation heat treatment temperature)
[0058] The process steps of Example 3 and Example 1 are basically the same, the main difference is that in Example 3, the insulation temperature during the pre-lithiation process is changed from 800° C. to 600° C., and the other experimental conditions are kept unchanged.
[0059] Example 4 (Changing the heat treatment temperature during alkali reduction process)
[0060] The process steps of Example 4 and Example 1 are basically the same, the main difference is that the holding temperature of the heat treatment of the TiO2 and silicon oxide negative electrode reaction during the alkali reduction process in Example 4 is changed from 850° C. to 550° C. The other experimental conditions remain unchanged.
[0061] Example 5 (Changing the type of protective gas)
[0062] The process steps of Example 5 and Example 1 are basically the same, and the main difference is that in Example 5, argon is used instead of nitrogen as the protective atmosphere during the pre-lithiation process and the TiO2 de-alkali process. The other experimental conditions remain unchanged.
[0063] Example 6 (Changing the mass ratio of pre-lithium silicon oxide and TiO2)
[0064] The process steps of Example 6 and Example 1 are basically the same, the main difference is that in Example 6, the mass ratio of pre-lithium silicon oxide to TiO2 in the alkali reduction process is changed from 98:2 to 97:3, and the other experimental conditions are kept unchanged.
[0065] Example 7 (Changing the mass ratio of pre-lithium silicon oxide and TiO2)
[0066] The process steps of Example 7 and Example 1 are basically the same, the main difference is that in Example 7, the mass ratio of pre-lithium silicon oxide to TiO2 in the alkali reduction process is changed from 98:2 to 95:5, and the other experimental conditions are kept unchanged.
[0067] Example 8 (Changing the mass ratio of pre-lithium silicon oxide and TiO2)
[0068] The process steps of Example 8 and Example 1 are basically the same, the main difference is that in Example 7, the mass ratio of pre-lithium silicon oxide to TiO2 in the alkali reduction process is changed from 98:2 to 99:1, and the other experimental conditions are kept unchanged.
[0069] Comparative Example 1
[0070] The process steps of Comparative Example 1 and Example 1 are basically the same, the main difference is that the TiO2 alkali reduction treatment process is removed in Comparative Example 1. The other experimental conditions remain unchanged.
[0071] The specific steps are: SiO and LiH are mixed evenly at a mass ratio of 15:1, and the mixture is placed in a corundum crucible. Then the corundum crucible is transferred to a tube furnace, and argon is used as a protective gas throughout the process. The temperature is raised to 800°C at a heating rate of 5°C / min and kept for 6 hours, and then naturally cooled to room temperature. After the reaction is completed, a pre-lithiated silicon-oxygen negative electrode material is obtained.
[0072] Comparative Example 2 (Changing the mass ratio of pre-lithium silicon oxide and TiO2)
[0073] The process steps of Comparative Example 2 and Example 1 are basically the same, the main difference is that in Comparative Example 2, the mass ratio of pre-lithium silicon oxide to TiO2 in the alkali reduction process is changed from 98:2 to 99.9:0.1, and the other experimental conditions are kept unchanged.
[0074] Comparative Example 3 (Changing the mass ratio of pre-lithium silicon oxide and TiO2)
[0075] The process steps of Comparative Example 3 and Example 1 are basically the same, the main difference is that in Comparative Example 3, the mass ratio of pre-lithium silicon oxide to TiO2 in the alkali reduction process is changed from 98:2 to 90:10, and the other experimental conditions are kept unchanged.
[0076] Experimental Example 1
[0077] The physical and chemical properties of the silicon-oxygen negative electrode materials prepared in Examples 1-8 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1.
[0078] Specific surface area test method: measure the amount of gas adsorbed on the solid surface at different relative pressures, and then calculate the monolayer adsorption amount of the sample based on the Brunaue-Emmett-Teller (BET formula).
[0079] Material tap density test method: The tap density is tested using the Quantachrome AutoTap tap density meter.
[0080] Material pH value test method: pH meter test.
[0081] Table 1 Physical and chemical properties of silicon oxide negative electrode materials of Examples 1-8 and Comparative Examples 1-3
[0082] <![CDATA[Apparent density of material / g / cm 3 > <![CDATA[Specific surface area of material / m 2 / g]]> Material pH Example 1 0.88 6.2 9.6 Example 2 0.87 7.2 10.2 Example 3 0.87 5.5 10.0 Example 4 0.85 5.7 9.8 Example 5 0.86 5.9 9.6 Example 6 0.87 6.1 9.4 Example 7 0.84 5.8 9.1 Example 8 0.81 5.7 9.9 Comparative Example 1 0.87 6.5 11.2 Comparative Example 2 0.88 6.3 11.0 Comparative Example 3 0.91 5.8 9.3
[0083] From the test data in Table 1, it can be seen that the method of mixing a small amount of TiO2 with pre-lithiated SiO has no obvious effect on the tap density and specific surface area of the material.
[0084] From the pH values of the materials in Example 1 and Comparative Example 1, it can be seen that the use of TiO2 to reduce the alkalinity of the pre-lithiated SiO effectively reduces the alkalinity of the material surface, and the pH value can be reduced from 11.2 to 9.6. From the pH values of Example 1, Example 6, Example 7, Example 8 and Comparative Example 2, it can be seen that as the amount of TiO2 increases, the alkalinity of the material surface decreases more significantly.
[0085] Experimental Example 2
[0086] The silicon-oxygen negative electrode materials prepared in Examples 1-8 and Comparative Examples 1-3 were used to prepare half-cells, and the electrochemical performance of the half-cells was tested. The test results are shown in Table 2.
[0087] In the half-cell, the obtained silicon-oxygen negative electrode material, conductive carbon black SP, single-walled carbon nanotubes (SCNTs), and polyacrylic acid (PAA) are mixed together in a mass ratio of 85.75:3:0.5:10 with water as a dispersant to prepare a slurry. The obtained slurry is coated on a copper foil current collector, and then dried, rolled, and cut to obtain a negative electrode sheet.
[0088] The half-cell uses metallic lithium as the negative electrode, with a voltage range of 0.005-1.5V. During discharge, the current density is first discharged at a constant current of 0.05C to 0.05V, then discharged at a constant current of 0.2C to 0.005V, left to stand for 20 minutes, and charged at a constant current of 0.05C to 1.5V.
[0089] Table 2: Electrochemical performance of half-cells
[0090]
[0091] It can be seen from the data in Table 2 that one or more of the parameters of the silicon-oxygen negative electrode materials provided in Comparative Examples 1 to 3 are not within the scope of the present invention, and the half-cell electrochemical performance of these silicon-oxygen negative electrode materials is poor. The half-cell electrochemical performance of the silicon-oxygen negative electrode materials provided in Examples 1 to 8 is better.
[0092] See Table 2 for data and Appendix Figure 1-2 It can be seen that compared with Example 1, by adding TiO2, the first delithiation capacity of the half-cell, the first coulombic efficiency of the half-cell (cut-off voltage 1.5V), the capacity retention rate of the half-cell after 100 cycles, and the capacity retention rate at high current density are all improved, among which the first delithiation capacity of the half-cell is increased by 0.8% (1402.8 / 1391.7*100%-100%=0.8%); the first coulombic efficiency of the half-cell is increased by 3.1% (91.23 / 88.49*100%-100%=3.1%), the capacity retention rate of the half-cell after 100 cycles is increased by 3.9% (72.16 / 69.45*100%-100%=3.9%), and the capacity retention rate at high current density is increased by 23.9% (36.42 / 29.4*100%-100%=23.9%).
[0093] From the experimental data of Examples 1, 6, 7, and 8, it can be seen that when the mass ratio of pre-lithium silicon oxide to TiO2 is 95-99:1-5, the electrochemical performance of the battery is better, among which when the mass ratio of pre-lithium silicon oxide to TiO2 is 98:2, the electrochemical performance of the battery is the best.
[0094] It can be seen from the experimental data of Example 1 and Comparative Example 2 that when the mass ratio of pre-lithium silicon oxide to TiO2 is changed from 98:2 to 99.9:0.1, the TiO2 content is too low, resulting in low reaction activity of TiO2 with alkaline substances and insignificant effect of removing alkaline substances. Therefore, the electrochemical performance is similar to that of pre-lithium silicon oxide without alkali reduction treatment.
[0095] From the experimental data of Example 1 and Comparative Example 2, it can be seen that when the mass ratio of pre-lithium silicon oxide to TiO2 is changed from 98:2 to 90:10, the TiO2 content is too high, resulting in a decrease in the content of negative electrode active materials and a significant decrease in specific capacity. Although lithium titanate is a conductor with good ionic conductivity, its electronic conductivity is poor. Excessive TiO2 and lithium titanate in the negative electrode material reduce the electronic conductivity of the negative electrode, which leads to a decrease in its rate performance.
[0096] Therefore, the present invention adopts a method of mixing a small amount of TiO2 with pre-lithiated SiO2 to convert the residual alkali on the surface of the pre-lithiated SiO2 negative electrode material into electrochemically active lithium titanate in situ. While reducing the alkalinity of the surface of the negative electrode material, it also enhances its ion conductivity and electrochemical reaction activity.
[0097] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, change of structural morphology, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0098] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0099] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0100] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0101] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for reducing the alkalinity of the surface of pre-lithium silicon oxide, characterized in that: The steps include: S1, pre-lithiation treatment of SiO using lithium reagent; S2, mixing the pre-lithiated SiO and TiO2; S3. Heat-treating the mixed SiO and TiO2.
2. The method for reducing the surface alkalinity of pre-lithium silicon oxide according to claim 1, characterized in that: In S1, the lithium reagent is selected from one of LiOH, Li2CO3, and LiH.
3. The method for reducing the surface alkalinity of pre-lithium silicon oxide according to claim 1, characterized in that: In S1, the mass ratio of SiO and lithium reagent is 10:1-15:
1.
4. The method for reducing the alkalinity of the pre-lithium silicon oxide surface according to claim 1, characterized in that: In S1, the pre-lithiation treatment temperature is 600-800°C and the time is 3-6h.
5. The method for reducing the surface alkalinity of pre-lithium silicon oxide according to claim 1, characterized in that: In S1, during the pre-lithiation treatment, nitrogen or argon is introduced as a protective gas.
6. The method for reducing the alkalinity of the pre-lithium silicon oxide surface according to claim 1, characterized in that: In S2, the mass ratio of SiO and TiO2 after pre-lithiation is 95:5 to 99:
1.
7. The method for reducing the surface alkalinity of pre-lithium silicon oxide according to claim 6, characterized in that: In S2, the mass ratio of SiO and TiO2 after pre-lithiation is 98:
2.
8. The method for reducing the alkalinity of the pre-lithium silicon oxide surface according to claim 1, characterized in that: In S3, the reaction temperature of the heat treatment process is 500-900°C, and the reaction time is 3-6h.
9. The method for reducing the alkalinity of the pre-lithium silicon oxide surface according to claim 1, characterized in that: In S3, the heating rate of the heat treatment process is 1-5°C / min.
10. The method for reducing the alkalinity of the surface of pre-lithium silicon oxide according to claim 1, characterized in that: In S3, during the heat treatment, nitrogen or argon is introduced as a protective gas.